2022
DOI: 10.3390/diagnostics12040870
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Power of cfDNA, CTCs and EVs in Oncology

Abstract: Liquid biopsy is a promising technique for clinical management of oncological patients. The diversity of analytes circulating in the blood useable for liquid biopsy testing is enormous. Circulating tumor cells (CTCs), cell-free DNA (cfDNA) and extracellular vesicles (EVs), as well as blood cells and other soluble components in the plasma, were shown as liquid biopsy analytes. A few studies directly comparing two liquid biopsy analytes showed a benefit of one analyte over the other, while most authors concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 168 publications
0
21
0
Order By: Relevance
“…56 Their role in liquid biopsy complements ctDNA and CTC analysis, enhancing the diagnostic spectrum and offering a noninvasive avenue for comprehensive tumor evaluation. 29,57 While the value of traditional biopsies is unequivocal, the noninvasive nature of liquid biopsies allows for a complementary approach. They facilitate ongoing monitoring of genetic changes, enabling clinicians to adapt treatment strategies in real time.…”
Section: Challeng E S and Limitati On S In D Iver S E B I Opsy Flu Idsmentioning
confidence: 99%
“…56 Their role in liquid biopsy complements ctDNA and CTC analysis, enhancing the diagnostic spectrum and offering a noninvasive avenue for comprehensive tumor evaluation. 29,57 While the value of traditional biopsies is unequivocal, the noninvasive nature of liquid biopsies allows for a complementary approach. They facilitate ongoing monitoring of genetic changes, enabling clinicians to adapt treatment strategies in real time.…”
Section: Challeng E S and Limitati On S In D Iver S E B I Opsy Flu Idsmentioning
confidence: 99%
“…To overcome these limitations for early cancer detection, a combination of other circulating biomarkers (e.g., ctDNA, extracellular vesicles-EVs, miRNAs, proteins, etc.) should be considered …”
Section: Challenges and Perspectives In Ctc Analyses For Medical Diag...mentioning
confidence: 99%
“…should be considered. 182 Medical diagnosis based on CTC enumeration and characterization could also benefit from answering fundamental questions regarding biological features of CTCs throughout the metastatic cascade; for example, limited information is known regarding CTC life cycle or their dissemination rhythm in the bloodstream. A recent study observed accelerated CTC dissemination during sleep in mBRCA patients and that these rest-phase CTCs presented a higher metastatic potential compared to active-phase CTCs.…”
Section: Analyses For Medical Diagnosismentioning
confidence: 99%
“…Evidence suggests that the sensitivity and specificity of cfDNA assays may not only be augmented by the simultaneous interrogation of multiple cfDNA features, but also by the parallel characterization of cfDNA and other biomarkers, such as proteins [ 331 , 332 ], genomic DNA and RNA from circulating tumor cells (CTCs) [ 333 , 334 , 335 , 336 , 337 , 338 , 339 , 340 ], EVs [ 338 , 341 ], miRNAs [ 342 , 343 ], metabolites [ 344 ], or mRNA transcripts [ 345 ].…”
Section: Multimodal Analysis Data Integration and Machine Learning (Ml)mentioning
confidence: 99%